An exploratory investigation into factors affecting class attendance in a hospitality management module. - Braak, Doulette (My University, 2015)
The research investigates various factors that influence student class attendance in a Hospitality Management module. Using survey questionnaires, the research aimed to determine factors that may negatively affect class attendance of first year students. The research was embarked upon to determine reasons for students not attending class as a possible variable for low throughput and high dropout rates. The research findings will indicate which factors affects class attendance the most in a Hospitality Management module. The data was analysed according to biographical information, external factors influencing class attendance, students’ motivation, respondents’ perceptions and internal factors to the institution. The biographical information does not play a factor in absenteeism. External factors do play a very small factor in non-attendance, what but no a significant role. The research found that motivation, respondents’ perceptions and internal factors to the institution do play a role in non-attendance in group of students.
Keywords: Class attendance; Hospitality management; Student motivation